ケモカインCX3CL1の腹腔投与による認知機能老化の改善 - 中瀬古（泉）, 寛子; 武井, 義則; 後藤, 愛; 神林, 隆一; 杉山, 篤 (日本薬理学会年会要旨集, 2022)
Aging is associated with a progressive decline in cognitive function. While obesity accelerates aging process of the brain,physical activity preserves and improves cognitive performance in the elderly. The expression of a chemokine CX3CL1 has been reported to be increased in both conditions. CX3CL1 is known to chemoattract T cells and monocytes. Moreover, it promotes survival of neurons in the brain and b-cells in the pancreas. In adipose tissues, it is expressed in adipose cells and attenuates effects of obesity-induced chronic inflammation. However, the role of the lifestyle-induced CX3CL1 expression in cognitive aging is unknown. Here, we administered CX3CL1 into the peritoneal cavity of aged mice (15-16 months old) to investigate its impact on the aging process of cognition. In the hippocampus, CX3CL1 increased the number of Type-2 neural stem cells and promoted brain-derived neurotrophic factor (BDNF) expression. This treatment, furthermore, improved novel object recognition memory impaired with advancing age. Intraperitoneal transplantation of peritoneal cells from CX3CL1-treated aged mice improved novel object recognition memory in recipient aged mice. Vagotomy inhibited the CX3CL1-induced increase in BDNF expression. Thus, our results demonstrate that a novel connection among peritoneal cells, the vagal nerve and the hippocampus can reverse the age-associated decline in recognition memory.